2004
DOI: 10.1007/s10549-004-8691-1
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical detection of epithelial cells in the bone marrow of primary breast cancer patients: a meta-analysis

Abstract: We conclude that the finding of epithelial cells in BM of BC patients correlates with several known prognostic factors and has adverse impact in the DFS and OS of these patients that seems, however, to decrease with time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
(38 reference statements)
1
5
0
6
Order By: Relevance
“…These results are in agreement with the studies of Braun and Schindlbeck, where established pathological parameters did not predict the presence of ICC-detected CK þ in BM samples Schindlbeck et al, 2004). However, in the meta-analysis of Weinschenker, a direct correlation was observed between ICC BM positivity and the primary tumour's presence with expression of ER, large size and higher histologic grade (Weinschenker et al, 2004). In the study of Pierga et al, the presence of ICC CK þ cells in blood in patients with operable disease was correlated with negative ER and nodal involvement.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in agreement with the studies of Braun and Schindlbeck, where established pathological parameters did not predict the presence of ICC-detected CK þ in BM samples Schindlbeck et al, 2004). However, in the meta-analysis of Weinschenker, a direct correlation was observed between ICC BM positivity and the primary tumour's presence with expression of ER, large size and higher histologic grade (Weinschenker et al, 2004). In the study of Pierga et al, the presence of ICC CK þ cells in blood in patients with operable disease was correlated with negative ER and nodal involvement.…”
Section: Discussionsupporting
confidence: 91%
“…In these studies, the BM status is considered as a mirror for the efficacy of the metastatic process throughout the body, similar to detection of cancer cells in lymph nodes. Also, the prognostic relevance of DECs in BM is clearly demonstrated by a number of large studies Weinschenker et al, 2004). The vast majority of these studies used immunocytochemistry for cell detection.…”
mentioning
confidence: 99%
“…Numerous studies have concluded that the presence of DTC in BM, evaluated by ICC or RT-PCR, correlates strongly with an early relapse of breast cancer and decreased patient survival (Landys et al 1998, Mansi et al 1999, Braun et al 2000b, Gebauer et al 2001, Gerber et al 2001, Wiedswang et al 2003, Schindlbeck et al 2004, Weinschenker et al 2004, Pantel & Woelfle 2005, Benoy et al 2006. As demonstrated by clinical follow-up data on more than 4000 breast cancer patients studied in prospective trials by several international groups, the presence of DTC in BM (identified by ICC at primary diagnosis) predicts the postoperative occurrence of overt metastases in bone and other organs (Braun et al 2005).…”
Section: Prognosis and Correlationsmentioning
confidence: 99%
“…В ходе ис-следований были объединены неспецифические эпителиальные маркеры и специфические маркеры РМЖ. Установлено, что мультимаркерный подход при ПЦР-диагностике является наиболее эффектив-ным для выявления микрометастазов РМЖ в КМ [10][11][12][13][14][15][16].…”
Section: актуальная темаunclassified